CA10 and CA11 negatively regulate neuronal activity‐dependent growth of gliomas. Issue 5 (20th March 2019) - Tao, Bangbao; Ling, Yiqun; Zhang, Youyou; Li, Shu; Zhou, Ping; Wang, Xiaoqiang; Li, Bin; Jun, Zhong; Zhang, Wenchuan; Xu, Chunyan; Shi, Juanhong; Wang, Lifeng; et al.
Abstract : Recent studies have revealed that neurons can promote glioma growth through activity‐dependent secretion of neurotrophins, especially neuroligin‐3. It has therefore been suggested that blocking neuron‐derived neurotrophins may serve as a therapeutic intervention for gliomas. Carbonic anhydrase‐related proteins 11 and 10 (CA11 and CA10) are secreted synaptic proteins which function as neurexin ligands, and the gene‐encoding CA11 is part of a gene signature associated with radiotherapy and prognosis in gliomas. We therefore hypothesized that CA11/CA10 might participate in the neuronal activity‐dependent regulation of glioma growth. In this study, we report that CA11 secreted by depolarized cultured neurons within conditioned medium (CM) inhibited the growth of glioma cell lines. CM from depolarized neurons inhibited CA11 expression in glioma cell lines via the Akt signaling pathway. Consistently, CA11 expression was also reduced in clinical glioma samples and negatively associated with high histological grade. Low CA11 expression of gliomas was associated with short survival in four independent datasets [repository of brain neoplasia data (REMBRANDT), The Cancer Genome Atlas (TCGA) lower grade glioma (LGG), GSE4271, andGSE42669 ]. CA11 knockdown promoted cell growth, clone formation, and migration; inhibited apoptosis; and increased tumor size in xenografted nude mice. Similarly, CA10 and CA10 secreted by depolarized cultured neurons also inhibited the growth of glioma cell lines. Low CA10 expression was associated with short survival in REMBRANDT, TCGA LGG, and GEOGSE4271 datasets. Our results suggest that CA11 and CA10 negatively regulate neuronal activity‐dependent glioma growth and inhibit glioma aggression. Thus, CA11/CA10 may represent a potential therapeutic target for the treatment of gliomas. Abstract : Carbonic anhydrase‐related proteins 11 and 10 (CA11 and CA10) are secreted synaptic proteins which function as neurexin ligands. Here, we report that CA10 and CA11 secreted by depolarized cultured neurons inhibited the growth of glioma cell lines. CA10 and CA11 expression was reduced in clinical glioma samples and associated with survival. Thus, CA11 and CA10 negatively regulate neuronal activity‐dependent glioma growth.